The ethics of death - Steffen, Lloyd H., 1951-; Cooley, Dennis R., 1965- (Minneapolis: : Fortress Press, 2014)
"For the living, death has a moral dimension. When we confront death and dying in our own lives and in the lives of others, we ask questions about the good, right, and fitting as they relate to our experiences of human mortality. When others die, the living are left with moral questions--questions that often generate personal inquiry as to whether a particular death was "good" or whether it was tragic, terrifying, or peaceful. In The Ethics of Death, the authors, one a philosopher and one a religious studies scholar, undertake an examination of the deaths that we experience as members of a larger moral community. Their respectful and engaging dialogue highlights the complex and challenging issues that surround many deaths in our modern world and helps readers frame thoughtful responses. Unafraid of difficult topics, Steffen and Cooley fully engage suicide, physician-assisted suicide, euthanasia, capital punishment, abortion, and war as areas of life where death poses moral challenges." -- Publisher's description.
Ethical perspectives -- Abortion -- The death penalty -- War -- Suicide -- End of life I: Physician assisted suicide -- The end of life II: Futility/euthanasia -- The value of death / Lloyd Steffen.
Cover subtitle: Religious and philosophical perspectives in dialogue.
Includes bibliographical references and indexes.
Keywords: Death -- Moral and ethical aspects; Abortion -- Moral and ethical aspects; Capital punishment -- Moral and ethical aspects; Suicide -- Moral and ethical aspects; Euthanasia -- Moral and ethical aspects